OLEH-OLEH ALTERNATIF GALAMAI BUAH MATOA SEBAGAI CIRI KHAS KABUPATEN KUANTAN SINGINGI - Almiska, Popi Septi; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Souvenirs are an important part of a tourist city, one of the potential attractions that supports the development of tourist areas is typical food. And this research aims to create an alternative to matoa fruit galamai to improve the procedure for making galamai with various fruit flavors such as matoa fruit. If you already know the steps for making matoa fruit galamai products, it will be an inspiration of knowledge for people who want to increase their income by opening a business. The method used in this research is qualitative description. The result of this research is the very distinctive taste of matoa fruit, its chewy texture is brownish in color. The packaging color used is white. What is contained in this research is of course intended to be able to apply the new strategies obtained and as a reference for further research regarding new alternatives to this matoa fruit. Keywords: Typical food, Souvenirs, Alternatives